2020
DOI: 10.3892/etm.2020.8950
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels of CXCR4 and CXCL12 in patients with rheumatoid arthritis and its correlation with disease activity

Abstract: The present study aimed to investigate the expression levels of C-X-C motif chemokine receptor 4 (CXCR4) and CXC ligand 12 (CXCL12) in patients with rheumatoid arthritis (RA) and the correlation with disease activity. In total, 60 patients with RA were selected as the study group, comprising of 28 patients in active-stage and 32 patients in remission-stage. In addition, 60 patients with osteoarthritis were selected as the control group. Western blotting and ELISA were used to detect the expression of CXCR4 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 50 publications
5
17
0
Order By: Relevance
“…Further reinforcing this impression of dysregulated humoral immunity, we saw increased CXCR4 expression, a common feature of autoantibody mediated autoimmune diseases, such as SLE [38][39][40] . Increased CXCR4 on B-cells or T-cells may allow them to home towards extrafollicular sites and potentially disrupt light zone organization in germinal centers 41 .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Further reinforcing this impression of dysregulated humoral immunity, we saw increased CXCR4 expression, a common feature of autoantibody mediated autoimmune diseases, such as SLE [38][39][40] . Increased CXCR4 on B-cells or T-cells may allow them to home towards extrafollicular sites and potentially disrupt light zone organization in germinal centers 41 .…”
Section: Discussionsupporting
confidence: 61%
“…The balance between CXCR4 and CXCR5 in B-cells is believed to play a key role in autoimmune disorders such as Systemic lupus erythematosus (SLE) and Rheumatoid arthritis, demonstrated by increases in a CXCR4 + CXCR5 lo subset in SLE [38][39][40] . We observed downregulation of CXCR5 expression by non-plasma B-cells in severe COVID-19 patients (Fig.…”
Section: Since We Had Observed Increased Cxcr4 Expression By Cd4 T Cells From Covid-19mentioning
confidence: 99%
“…The CXCR4 and CXCL12 expression levels in serum and joint synovial fluid of the study group were found to be markedly higher than those of controls (Peng et al. 2020 ). The level of CXCL12 decreased in the serum of patients with RA after synovectomy (Kanbe et al.…”
Section: Discussionmentioning
confidence: 93%
“…This CXCR4-mediated dual anti-IFN and anti-inflammatory activity may provide clinical benefits as type I IFNs are widely detected and functionally active in RA [27]. Interestingly, a recent study shows that the levels of CXCR4 and its natural ligand, CXCL12 are significantly higher in the serum and joint synovial fluids of active RA patients compared to the control group [28].…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, CXCR4 and CXCL12 expression levels in the RA active group are higher compared to the remission group [28]. Higher accessibility to CXCR4 in RA patients makes targeting the CXCR4 anti-inflammatory pathway a particularly promising strategy for these pathologies.…”
Section: Discussionmentioning
confidence: 99%